IMPLEMENTASI MODEL PEMBELAJARAN DIRECT INSTRUCTION UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Meyta P Pritandhari (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
The learning model is basically a form of learning which is illustrated from the opening to the closing that is typically presented by teachers or lecturers. While the method of learning is the way used to implement the plan that has been prepared in the real activity for the objectives that have been compiled achieved optimally.Direct instruction model can encourage students' skill to build their own knowledge through learning activities. The learning activities provided are by giving the exercises directly. Giving the tasks directly by providing a problem that must be solved by students so that students are expected to be active to deepen the material provided.The implementation of direct instructioncan improve students' creative thinking skill. This is evident from the the students’ skill in presenting the results of observations that they have done. They have broader thoughts and insights because they have learned from the firsthand. Direct instruction can provide a meaningful experience in learning.Keywords: Creative thinking, Direct instruction, Learning model